ADVANCED METHODOLOGIES FOR MONITORING CONTAMINATED WATER AND HUMAN HEALTH: AN AI-DRIVEN OVERVIEW OF WATERBORNE DISEASE (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2026)
Waterborne diseases resulting from contaminated water sources remain a critical threat to global public health and economic stability. This paper provides a comprehensive academic overview of the intersection between hydrological contamination and human health, proposing an advanced, artificially intelligent surveillance methodology. By integrating environmental exposomics with continuous physiological monitoring, we aim to modernize the epidemiological response to waterborne pathogen outbreaks. The proposed theoretical framework highlights the necessity of multimodal data fusion to accurately predict, track, and mitigate the spread of aquatic pathogens.